Suffering from Loneliness Indicates Significant Mortality Risk of Older People - Reijo S. Tilvis; Venla Laitala; Pirkko E. Routasalo; Kaisu H. Pitkälä (Journal of Aging Research)
Background. The harmful associates of suffering from loneliness are still in dispute. Objective. To examine the association of feelings of loneliness with all-cause mortality in a general aged population. Methods. A postal questionnaire was sent to randomly selected community-dwelling of elderly people (>74 years) from the Finnish National Population Register. The questionnaire included demographic characteristics, living conditions, functioning, health, and need for help. Suffering from loneliness was assessed with one question and participants were categorized as lonely or not lonely. Total mortality was retrieved from the National Population Information System. Results. Of 3687 respondents, 39% suffered from loneliness. Lonely people were more likely to be deceased during the 57-month follow-up (31%) than subjects not feeling lonely (23%, 𝑃<.001). Excess mortality (HR=1.38, 95% CI=1.21-1.57) of lonely people increased over time. After controlling for age and gender, the mortality risk of the lonely individuals was 1.33 (95% CI=1.17-1.51) and after further controlling for subjective health 1.17 (CI=1.02-1.33). The excess mortality was consistent in all major subgroups. Conclusion. Suffering from loneliness is common and indicates significant mortality risk in old age.